PERENCANAAN STRUKTUR GEDUNG RUANG BELAJAR SMP TERPADU AL-MUNIR MENGGUNAKAN PROGRAM SAP2000: Studi Kasus SMPT AL-Munir Tasikmalaya - Fahriana, Rifqi; Defiana, Yanti; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
In West Java Province, the demand for educational facilities continues to increase in line with population growth and the rising need for improved educational quality. The education sector plays a crucial role in supporting national development; therefore, it requires adequate facilities and infrastructure to ensure that teaching and learning activities can be conducted effectively. However, the existing educational facilities are still insufficient to meet current demands. SMP Terpadu AL-Munir, for instance, currently utilizes classrooms owned by the AL-Munir Foundation to support its learning activities. As the number of students, teachers, and supporting staff continues to grow, more representative and properly planned classroom buildings are required in accordance with educational building planning standards. This study aims to analyze and design the structural system of the Classroom Building of SMP Terpadu Al-Munir by utilizing SAP2000 software. The structural model is developed based on reinforced concrete design principles and incorporates a flexible structural system characterized by a high level of ductility. The result is in the design of beams, columns and plates using steel tensile capacity BJTS fy = 420 MPa dan BJTP fy = 280 MPa and concrete compressive capacity fc’ = 25 MPa. with beam design with size B1 = 35 cm x 50 cm with main tensile reinforcement 5 D16 and compression 3 D16, 2D10-100 sliding reinforcement on the pedestal area, 4D10-150 sliding reinforcement in the field area, 2D12 torsion reinforcement in fulcrum area and field, B2= 25 cm x 35 cm with main tensile reinforcement 5 D16 and compression 3 D16. The repeating of Column design is obtained with size K1 = 40 cm x 40 cm column is installed 16D16 flexural reinforcement,and 2D10-100 shear reinforcement in the fulcrum area and 2D10-150 shear reinforcement in the field area.K2 = 35 cm x 35 column is installed 16D16 flexural reinforcement,and 2D10-100 shear reinforcement in the fulcrum area and 2D10-150 shear reinforcement in the field area. K3 = 30 cm x 30 cm column is installed 16D16 flexural reinforcement,and 2D10-100 shear reinforcement in the fulcrum area and 2D10-130 shear reinforcement in the field area. Floor Plate design is obtained with thickness 12 cm with reinforcement in direction x = ∅ 12 -230 and direction y = ∅ 12 – 240, and roof Plate design is obtained with thickness 12 cm with reinforcement in direction x = ∅ 12 -200 and direction y = ∅ 12 - 200.